Lay Belief in Biopolitics and Political Prejudice. (March 2017) - Suhay, Elizabeth; Brandt, Mark J.; Proulx, Travis
Building on psychological research linking essentialist beliefs about human differences with prejudice, we test whether lay belief in the biological basis of political ideology is associated with political intolerance and social avoidance. In two studies of American adults (Study 1: N = 288, Study 2: N = 164), we find that belief in the biological basis of political views is associated with greater intolerance and social avoidance of ideologically dissimilar others. The association is substantively large and robust to demographic, religious, and political control variables. These findings stand in contrast to some theoretical expectations that biological attributions for political ideology are associated with tolerance. We conclude that biological lay theories are especially likely to be correlated with prejudice in the political arena, where social identities tend to be salient and linked to intergroup competition and animosity.